2001
DOI: 10.1515/crll.2001.030
|View full text |Cite
|
Sign up to set email alerts
|

1-2-3 theorem for curves on algebraic surfaces

Abstract: Theorem I. Let D be a 1-connected curve with K D nef and p a D Z 2. Let L, M be line bundles on D such that L À 2K D and M À 2K D are both nef. Then the multiplication map H 0 D; L n H 0 D; M 3 H 0 D; L M is surjective except in the following cases:(1) p a D 2 and L M 1 2K D .(2) D contains a curve E with p a E 1, ED À E 1 and L M 1 2K D on E.Here the symbol 1 means the numerical equivalence.Partially supported by Japan Association for Mathematical Sciences.Brought to you by | University of Arizona Authenticat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
24
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 7 publications
(7 reference statements)
0
24
0
Order By: Relevance
“…In this appendix, we state some results about canonical algebras of curves on a smooth surface in order to supplement [13].…”
Section: Proof Recall Thatmentioning
confidence: 99%
See 3 more Smart Citations
“…In this appendix, we state some results about canonical algebras of curves on a smooth surface in order to supplement [13].…”
Section: Proof Recall Thatmentioning
confidence: 99%
“…2 and K D is nef. In [13], we studied the canonical ring R(D; K D ) L m!0 H 0 (D; mK D ) and showed that it is generated in degrees 3.…”
Section: Proof Recall Thatmentioning
confidence: 99%
See 2 more Smart Citations
“…In Sect. 4, we restrict ourselves to (weakly) elliptic singularities [11] in order to clarify, to some extent, how our method relates to Yau's elliptic sequence [13]. When the fixed part corresponds to a rational double point of type A and the biggest loupe contracts to an elliptic singularity, Theorem 4.1 shows that the associated sequence of loupes is nothing more than the elliptic sequence.…”
mentioning
confidence: 99%